2007
DOI: 10.1177/10883576070220030301
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Social Communication Skills of Children With Autism Spectrum Disorders During Interactions With Typical Peers

Abstract: The Social-Communication Assessment Tool (S-CAT) Was created as a direct observation instrument to quantify specific social and communication deficits of children With autism spectrum disorders (ASD) Within educational settings. In this pilot study, the instrument's content validity and interrater reliability Were investigated to determine the degree to Which the S-CAT categorically discriminated betWeen children With ASD and those Without ASD. S-CAT ratings of 16 children With ASD Were compared to the ratings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 19 publications
0
19
0
4
Order By: Relevance
“…Murdock, Cost, and Tieso (2007) suggested that alterations to communication in AD can vary from absence of verbal communication to pragmatic deficits in otherwise fluent speech. Because of the significance of AD in development, it is important to understand compromises to very early communication in AD; in infants, this means facial expression and vocalization.…”
mentioning
confidence: 99%
“…Murdock, Cost, and Tieso (2007) suggested that alterations to communication in AD can vary from absence of verbal communication to pragmatic deficits in otherwise fluent speech. Because of the significance of AD in development, it is important to understand compromises to very early communication in AD; in infants, this means facial expression and vocalization.…”
mentioning
confidence: 99%
“…Younger children with ASD often fail to naturally develop and demonstrate joint attention, an early form of social interaction typically observed between a parent and toddler [3,4]. Continued difficulties as the child develops are observed in reduced number of social initiations and reciprocity in conversation and sustained conversation skills, compared to typically developing school aged children [5,6]. Finally, several studies have demonstrated reduced ability in individuals with ASD to recognize and correctly interpret emotional states from facial affect [7], vocal affect, [8], and video vignettes of interactions [9].…”
Section: Introductionmentioning
confidence: 99%
“…This is evident in many of behavioral manifestations that indicate weakness in social communication and poor social skills among children with Autism (Bellini & Hopf, 2007;Murdock, Cost, & Tieso, 2007). The social skills of students with Autism are among the fundamental objectives of many effective programs based on many of the strategies that take into account the characteristics of these students at the cognitive and social levels.…”
Section: Statement Of the Problemmentioning
confidence: 99%